Pengaturan Hukum Dan Prospek Penggunaan Artificial Intelligence Dalam Era Digitalisasi Sistem Peradilan Di Indonesia - Zahra Kamila (Jurnal Riset Multidisiplin Edukasi, 2025)
The application of Artificial Intelligence (AI) in Indonesia’s legal processes offers opportunities to enhance efficiency and transparency. However, existing regulations do not specifically address critical aspects such as ethics, accountability, and security. This study examines the current legal framework, prospects, and challenges of AI implementation within the criminal justice system in the digital era. The study employs a normative juridical method, analyzing relevant laws and regulations alongside a comparative study of practices in other countries. The data is analyzed qualitatively to identify regulatory gaps. The findings reveal that AI holds significant potential in improving the efficiency of legal document management. Nonetheless, major challenges persist, including algorithmic bias, data protection concerns, and institutional resistance to technological adoption. Specific regulations, strengthened digital infrastructure, and capacity-building programs for legal practitioners are urgently needed to ensure a fair and sustainable application of AI in the justice system.